Oxidation Ditch Reactor to Remove Ammonia and Phosphate in Tofu Wastewater and Skin Tanning Wastewater - Ni Made Maya Febriana Ramadhany; Savira Safrialia; Lolita Kurniasari; Iqbal Ramadhan; Euis Nurul Hidayah; Aulia Ulfa Farahdiba (Future Science)
Wastewater containing various types of environmental pollutants, for example, Ammonia and phosphate. Wastewater disposal without proper handling will have an impact on environmental quality degradation, so it is necessary to wastewater treatment using an oxidation ditch reactor with a capacity of 500 liters with an operational volume of 250 liters. The variation treatment in this study was by using tofu wastewater (T) and skin tanning wastewater (PK) with direct sunlight and aeration process with 60 rpm rotation speed for 24 hours x 7 days. The results showed (T) was able to reduce the ammonia concentration by 94.1% from a value of 0.18 mg/L to 0.07 mg/L and a phosphate concentration of 75.3% from a value of 16.05 mg/L to 3.96 mg/L. Whereas the (PK) able to reduce the ammonia concentration by 94.1% from a value of 0.18 mg/L to 0.07 mg/L and a phosphate concentration of 41.4% from a value of 10.2 mg/L to 5.9 mg/L.